Desain Sistem Kontrol Level Cairan Dengan Metode PID Berbasis PLC - Putri, Ratna Ika; Setiawan, Hendra Mars; Setiawan, Budhy; Wibowo, Sunu Hasta (P3M Politeknik Negeri Banjarmasin, 2022)
This article discusses the water level control of the tank using PID control which is implemented on PLC (Programmable Logic Control) with HMI interface. This plant system consists of a controlled tank, a sup-ply tank, a water level sensor, a water faucet in the form of a motorized valve, PLC and HMI. In previous studies, the plant system used usually only has a controlled tank without a supply tank so that the control of the system becomes simpler. However, in this study a supply tank was also used so that the flow of water flowing in controlling the water level would depend on the water level of the supply tank and the opening of the water faucet. This plant system with a tank that has an open outlet pipe is a classic system that is non-linear so linearization is needed in its control. In order for the system to be linearized, it is assumed that both the supply tank and the controlled tank only operate within a certain value range. The realiza-tion of a water level control system using a PID controller was made and tested for its effectiveness at the setpoint values of 10 cm and 20 cm. Based on the simulation and experimental results, it was found that the system worked well where the PID control was able to stabilize the system at both setpoint values where the obtained overshoot were below 10%.